Cumulative Mitoxantrone-Induced Haematological and Hepatic Adverse Effects in a Subchronic In vivo Study - Rossato, Luciana G. (2014)
Mitoxantrone (MTX) is an antineoplastic agent that can induce hepato- and haematotoxicity. This work aimed to investigate the occurrence of cumulative early and late MTX-induced hepatic and haematological disturbances in an vivo model. A control group and two groups treated with three cycles of 2.5 mg/kg MTX at days 0, 10 and 20 were formed. One of the treated groups suffered euthanasia on day 22 (MTX22) to evaluate early MTX toxic effects, while the other suffered euthanasia on day 48 (MTX48), to allow the evaluation of MTX late effects. An early immunosuppression with a drop in the IgG levels was observed, causing a slight decrease in the plasma total protein content. The early bone marrow depression was followed by signs of recovery in MTX48. The genotoxic potential of MTX was demonstrated by the presence of several micronuclei in MTX22 leucocytes. Increases in plasma iron and cholesterol levels in the MTX22 rats were observed, while in both groups increases in the unconjugated bilirubin, C4 complement, and decreases in the triglycerides, alanine aminotransferase, alkaline phosphatase and transferrin were found in plasma samples. On MTX 48, the liver histology showed more hepatotoxic signs, the hepatic levels of reduced and oxidized glutathione were increased, and ATP hepatic levels were decreased. However, the hepatic total protein levels were decreased only in the livers of MTX22 group. Results demonstrated the MTX genotoxic effects, haemato- and direct hepatotoxicity. While the haematological toxicity is ameliorated with time, the same was not observed in the hepatic injury.